การพัฒนาผงโรยข้าวรสบูดูจากปลานิลจิตรลดารมควันร้อน - อทิตา ชนะสิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research was aimed to develop new rice seasoning product from Budu-khaw-yum and hot-smoked Tilapia fish. In the first part, a suitable condition for hot smoking of Tilapia fish was studied by varying smoking time (1-3 h) and drying time (1-3 h) at 60 ºC. After smoking and drying properties of smoked fish were assessed in terms of moisture content, aw and flesh colour (L*, a*, b*). The results showed that the optimum condition for hot–smoked Tilapia fish was smoking at 60 ºC, 3 h and followed by drying at 60 ºC for 3 h, then smoked fish was ground and dried again under hot air dryer at 70 ºC for 2 h could produce good quality dried hot- smoked Tilapia fish powder. In the second part, Budu-khaw-yum seasoning recipe was selected by comparing two recipes using Acceptance test with 60 panelists. The most accepted recipe was the one containing shrimp paste. In the third part, a production of Budu-khaw-yam seasoning powder was studied by comparing effect of two drying processess (vacuum drying, 55 ºC, 1 h. 45 min and hot air drying 90 ºC, 4h.) on chemical and physical properties of Budu-khaw-yum powder at the same final moisture content of 1-2 % (w.b.). The results showed that drying Budu-khaw-yum seasoning using vacuum dryer produced Budu-khaw-yam powder which had higher L* and a* value than using hot air dryer. Although, aw, b*, Thiobabituric acid (TBA) and proximate composition were not different from using hot air dryer, but the total energy consumption of vacuum dryer was much less than using hot air dryer. Fourth part of this research, a suitable ratio (1:1, 2:1 and 3:1) between Budu- khaw-yam seasoning powder and hot-smoked Tilapia fish powder was determined by using acceptance test with 60 panelists. The accepted ratio of Budu-khaw-yam seasoning powder and hot-smoked Tilapia fish powder was 3 parts of Budu-khaw-yam seasoning powder to 1 part of hot-smoked Tilapia fish powder. Finally, the qualities of product during storage as to product was packed in laminated aluminium bag (PE/AL/PE) at 35 ºC. The result showed that when increasing storage time was changed color and smell qualities of hot–smoked Tilapia fish powder. The moisture content and TBA increased significantly and the overall acceptability score slightly decrease. However the value of aw were not significant difference. Throughout 20 days storage the total bacterial count were lower than 250 CFU/g and yeast mold count were lower than 10 CFU/g. The Budu-khaw-yum powder had increased in moisture content, aw and TBA when storage time was increasing. The color and odor were changed and the overall acceptability score was slightly decreased. Throughout storage time for 80 days, total bacterial count, yeast mold and staphylococcus aureus were lower than 10 CFU/g.